Mining & environment - Dhar, Bharat B. (New Delhi : A.P.H. Pub. Corp., 2000)
Compilation of keynote addresses delivered at different national and international conferences, symposiums, seminars, etc., with special reference to India.
Includes bibliographical references and index.
Keywords: Mineral industries -- Environmental aspects -- India